Correlation Between B line in Lung Ultrasound and Plasma NT-proBNP Level in Patients with Acute Heart Failure - Zaman, Md Hasan; Hosen, Md Imam; Moyaj, Farhana; Arzu, Jahanara; Osmany, Dmm F; Ahmed, Sheikh Foyez; Hossain, Muhammad Mobarack; Hossain, Muhammad Kamal; Ahmed, Chaudhury Meshkat (University Heart Journal, 2023)
Background: Acute heart failure (AHF) is a major cause of morbidity and mortality worldwide. Although this is a common cause of dyspnoea, its diagnosis still represents a challenge. Lung ultrasound (LUS) is an emerging point-of-care diagnostic tool. Objective: The aim of the study was to assess the Correlation between B line in lung ultrasound and plasma NT-proBNP level in patients with acute heart failure & thus to assess the predictive value of B line in patients with suspected acute heart failure. Materials and Method: Crosssectional observational study conducted in cardiology department of BSMMU from October 2020 to September 2021. Study procedure: 36 patients presenting with of shortness of breath or heart failure diagnosis were enrolled meeting inclusion and exclusion criteria. The number of B-lines by Lung Ultrasound was measured. Correlation between number of B-lines on lung ultrasonography and NT-proBNP level were analyzed. Results: There is a positive correlation between the number of B-lines and the NT-proBNP levels (r=0.55, p< 0.01) in acute heart failure patients. Conclusion: Patients presenting with acute shortness of breath with raised NTproBNP level, B line detection &quantification by lung ultrasound can be used as a tool for a faster diagnosis and decision-making on lung congestion in acute heart failure. University Heart Journal 2023; 19(1): 15-19